AB0427 Prevalence of metabolic syndrome in an algerian cohort of rheumatoid arthritis. Correlation with disease activity and functional status. (23rd January 2014) - Slimani, S.; Abbas, A.; Ben Ammar, A.; Kebaili, D.; Ali, E.H.; Rahal, F.; Abtroun-Benmadi, S.; Ladjouze-Rezig, A.
Abstract : Background: There is evidence that rheumatoid arthritis (RA) patients have an over-risk of cardiovascular disease. This is mainly due to an increase in the prevalence of metabolic syndrome (MS). The prevalence of MS among adults in Algeria is 17, 8%. Objectives: The aim of the study was to evaluate the prevalence of MS among RA patients in Algeria. Another aim was to evaluate the relationship between MS, inflammation biomarkers and disease scores (DAS28 and HAQ). Methods: The study was performed on a cohort of 249 patients meeting the ACR/EULAR criteria for RA, followed in 11 Algerian centers. A standard clinical evaluation was performed, along with blood samples taken to measure biochemical and inflammatory parameters. The diagnosis of MS was based on the NCEP/ATP III (MS+ if ≥3/5). Prevalence of MS was calculated, and patients were divided in two groups (MS+ and MS-). Comparison between the 2 groups was performed using a T-test. Results: Among 249 RA patients, 213 were female and 36 males of a mean age 50, 1±14, 5 years, disease duration 8, 4±7, 8 years, DAS28 3, 9±4, 8, CRP 11±16mg/L, ESR 41±26mm, HAQ 0, 81±0, 82, rheumatoid factor positive in 78, 5% cases, mean BMI 25, 3±5, 1kg/m 2 . The overall prevalence of MS was 13, 9% (CI95: 9, 5%>20, 1%), it was 14, 3% in males and 13, 8% in females. There was no correlation between the presence of MS and levels of CRP, DAS28, HAQ scores, morning stiffness, RF, ACPA and presence of erosions. However, The ESR level was significantly higher in MS+ patients than in MS- patients (p=0, 036) (see table 1 ). Conclusions: In this multicenter study, unlike most studies on RA patients, the prevalence of MS was as high in Algerian RA patients (13, 9%) as in the Algerian general population (17, 8%). ESR levels correlate with the presence of MS and thus go with the conclusions drawn on occidental cohorts. However, CRP and DAS28 levels do not, this may be due to the moderate cohort size and needs to be confirmed. This reinforces the role of inflammation in RA on cardiovascular disease in those patients or the role of metabolic syndrome on systemic inflammation. A further analysis is scheduled at follow-up to determine whether disease control can reverse the clustering of MS in RA. Disclosure of Interest: None Declared